2019
DOI: 10.1007/s41109-019-0164-x
|View full text |Cite
|
Sign up to set email alerts
|

Bot stamina: examining the influence and staying power of bots in online social networks

Abstract: This study presents a novel approach to expand the emergent area of social bot research. We employ a methodological framework that aggregates and fuses data from multiple global Twitter conversations with an available bot detection platform and ultimately classifies the relative importance and persistence of social bots in online social networks (OSNs). In testing this methodology across three major global event OSN conversations in 2016, we confirmed the hyper-social nature of bots: suspected social bot accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
1
10
0
1
Order By: Relevance
“…The frequency and intensity of the bots we detected resembled those of previous studies (Bessi and Ferrara 2016;Forelle et al 2015;Schuchard et al 2019). Nonetheless, we did not detect the intent to engage other users in conversation, as seen in the bots detected in previous studies.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The frequency and intensity of the bots we detected resembled those of previous studies (Bessi and Ferrara 2016;Forelle et al 2015;Schuchard et al 2019). Nonetheless, we did not detect the intent to engage other users in conversation, as seen in the bots detected in previous studies.…”
Section: Discussionsupporting
confidence: 66%
“…Previous research focused on creating techniques to automatically identify bots by analyzing messaging behavior in the Twitter ecosystem (Schuchard et al 2019;Badawy et al 2019;Lai et al 2019;Wang et al 2020;Zheng et al 2019). Bots' movement throughout Twitter was primarily analyzed so as to improve automatic detection systems.…”
Section: Political Bots: Identification and Social Impactmentioning
confidence: 99%
“…Similarly, Broniatowski et al (2018) found that bots often are able to erode public consensus and promote harmful misinformation, such as anti-vaccination propaganda. The effects of bots pose serious implications, as work from Schuchard et al (2019) indicates that bots are hyper-social accounts that display a disproportionately high level of structural network influence online. Thus, this implies that the online reach of bots spans far beyond the reach of an average human user (Schuchard et al, 2019).…”
Section: Online Disinhibition Effectmentioning
confidence: 99%
“…The effects of bots pose serious implications, as work from Schuchard et al (2019) indicates that bots are hyper-social accounts that display a disproportionately high level of structural network influence online. Thus, this implies that the online reach of bots spans far beyond the reach of an average human user (Schuchard et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such a strategy is indeed used by the bots to remain unveiled and, thus, attract humans that are encouraged to interact with automatic-generated content. Similarly, in [15], the relative importance and persistence of social bots were analyzed during 3 crucial events, namely: 2016 US presidential elections, the ongoing Ukrainian-Russian conflict, and the Turkish censorship implemented by the government. More specifically, the primary outcomes of the study showed that bots attempted to initiate contact with users at an extremely higher rate than human users.…”
Section: Up Psoe Cs Pp Voxmentioning
confidence: 99%